Streptococcus lutetiensis neonatal meningitis with empyema. Issue 9 (13th September 2021) - Yu, Allen T.; Shapiro, Kate; Beneri, Christy A.; Wilks-Gallo, Lisa S.
Abstract : Streptococcus lutetiensis has been known to cause sepsis in adults, but only one case regarding neonatal sepsis has been reported internationally, with no sequelae. We report the first case of neonatal bacteremia and meningitis with empyema caused by S. lutetiensis in the United States.